Constructing 3D optical absorption holes by stacking macroporous membrane for highly efficient solar steam generation. (October 2020) - Guo, Chenglong; Zhao, Jiaxu; Zhang, Wenting; Miao, Endong; Xie, Yuhang
Abstract: In recent years, solar steam generation technology has received widespread attention in seawater desalination, but existence of some problems, namely difficulty in salt cleaning and high expense, limited it further development. Herein, in this work, a carbon black gauze membrane (CBGM), with low cost and easy to clean properties, was developed by stacking macroporous membrane to construct 3D optical absorption holes, which were favorable to an enhancement of light absorption. The 4-layer CBGM evaporation device displayed an improved solar steam generation performance, which was corresponded to the evaporation rate of 1.60 kg m −2 h −1 and the evaporation efficiency of 96.0% under 1 kW m −2, respectively. Likewise, the 4-layer CBGM evaporation device exhibited superior recyclability, long life and excellent desalination performance, as well as was able to effectively produce potable freshwater from seawater. Consequently, the CBGM was regarded as a promising alternative for high-efficiency solar-driven seawater desalination. Graphical abstract: Image 1 Highlights: A low-cost macroporous carbon black gauze membrane (CBGM) was developed. 3D optical absorption holes were constructed by stacking macroporous membrane. 4-layer CBGM promoted the evaporation rate to 1.60 kg m −2 h −1 at 1 kW m −2 . CBGM exhibited superior recyclability and excellent desalination performance.